SOLAR RADIATION ABSORPTION BY PLANT LEAVES - AL-Hassani, Dheyaa (Iraqi Journal of Science, 2024)
The aim of this research is to implement the model for solar radiation absorption byplant leaves to study the effects of season and time of the day on the absorbedamount of solar radiation. The effect of leaf area index, leaf angle distribution, leafabsorption coefficient were also considered. Calculations for the radiation fluxdensities for sunlit leaves, the radiation flux densities for shaded leaves, and theAbsorbed total Photosynthetically Active Radiation on the leaves were carried outfor Baghdad city (Latitude 33o N). The results showed that the behavior of sunlitleaves and shaded leaves behave differently as season and time of the day change.The leaf parameters have significant effect on the amount of solar radiation absorbedby the leaves.